On the solvability of a nonlinear optimization problem with boundary vector control of oscillatory processes - Abdyldaeva, E.F.; Kerimbekov, A.K.; Zhaparov, M.T. (Bulletin of the Karaganda University. Mathematics Series, 2023)
In the paper, the solvability of the nonlinear boundary optimization problem has been investigated for the oscillation processes, described by the integro-differential equation in partial derivatives with Fredholm integral operator. It has been established that the components of the boundary vector control are defined as a solution to a system of nonlinear integral equations of a specific form, and the equations of this system have the property of equal relations. An algorithm for constructing a solution to the problem of nonlinear optimization has been developed.